Morphology, ecology, and biogeography of new populations of Telmatobius pisanoi (Anura: Telmatobiidae) in the Eastern Cordillera, Salta, Argentina - Cruz, Julio César; Fabrezi, Marissa (Zootaxa, 2025)
The family Telmatobiidae consists of a single genus, Telmatobius, with 60 species distributed along the Andes of South America. Commonly known as water frogs, telmatobiids inhabit different types of mountain freshwater environments, with species ranging semi-aquatic to fully aquatic lifestyles. This study expands current knowledge of Telmatobius pisanoi by reporting two newly identified populations from the northern and northeast regions of the Calchaquí Valley, in the Eastern Cordillera of Salta province, north-western Argentina. We provide detailed morphological descriptions of adults, juveniles and tadpoles—including osteology and morphometric data—and compare them with previously known, geographically distant populations from the southern Calchaquí Valley and other species from Argentina. Based on the analysis of morphological variation and other biological aspects, we discuss the implications in the taxonomy, phylogeny, biogeography, natural history, and conservation of the species. Although intraspecific traits were consistent, the observed morphological variation suggests a historical fragmentation of populations. Additionally, we provide a distribution map integrating physical geography with both new field records and historical information contributed by local residents.